Experimental and simulated profiles of the Al XIII Ly-alpha resonance line from a cylindrically expanding plasma - Patel, P; Wark, J; Renner, O; Djaoui, A; Rose, S; Heading, D; Hauer, A (1997)
Spectral profiles of optically thick line radiation emitted by an expanding cylindrical laser-produced plasma have been recorded in high resolution using a vertical dispersion variant of the double-crystal spectrometer. By uniformly irradiating a narrow wire with a 1 ns pulse a quasi-steady plasma expansion is generated with a velocity gradient in excess of 10(9) s(-1). Such velocity fields strongly influence the transfer of radiation through a plasma, resulting in a complex distortion of the lineshapes of optically thick lines. We have computed theoretical profiles of the Al XIII Ly-alpha resonance line. Simulation of the laser-plasma interaction is performed using the 1D Lagrangian hydrocode MED103 which incorporates a non-LTE time-dependent excitation and ionisation package based on the average-atom model. Line emission profiles are calculated by the method of multi-frequency line transfer in the co-moving frame. We investigate the sensitivity of the lineshape on plasma parameters such as the velocity profile, comparing our theoretical predictions with experiment. (C) 1997 Published by Elsevier Science Ltd. All rights reserved.